INFLUENCE OF RENAL DYSFUNCTION ON THE LEVEL OF SERUM ANGIOPOIETIN-LIKE PROTEINS AND ANTI-PHOSPHOLIPID ANTIBODIES IN PATIENTS WITH RHEUMATOID ARTHRITIS AND METABOLIC SYNDROME - V. A. Aleksandrov (SPb RAACI, 2021)
Rheumatoid arthritis (RA) is a frequent background for the development of renal pathology. Chronic kidney disease (CKD) is determined in more than 30% of patients with RA. Along with inflammation and other factors in the progression of the underlying disease, the development of renal damage in RA is facilitated by the presence of metabolic syndrome (MetS).The aim of this study is to assess the relationship of serum concentrations of angiopoietin-like proteins (ANGPTL) and antiphospholipid antibodies (aPL) with the development of renal dysfunction in patients with RA.We examined 158 patients with RA (91.8% – women and 8.2% – men) aged 21 to 80 years old and an average duration of the disease – 9 (4-15) years. The majority of patients were seropositive for rheumatoid factor and for antibodies to cyclic citrullinated peptide, with an advanced clinical stage and moderate activity (3.2 < DAS28 ≤ 5.1) of the pathological process.The ELISA test was used for the quantitative determination of angiopoietin-like protein type 3 and type 4 and antibodies to phospholipids (aРL-IgG/IgM) for total detection of antibodies to cardiolipin, phosphatidylserine, phosphatidylinositol, phosphatidylic acid and a complex of negatively charged phospholipid and β2-glycoprotein-I.More than half of the examined RA patients had the calculated glomerular filtration rate (eGFR) ranging from 89 to 60 ml/min/1.73 m2 (allocation by CKD stages: C1 – 21.5%; C2 – 58.9%; C3 – 19.6%). Signs of MetS (a combination of increased blood pressure, increased triglyceride levels and carbohydrate metabolism disorders against the background of central obesity) were diagnosed in 68 (43%) RA patients. Multivariable analysis of variance was performed to compare the studied parameters (ANGPTL3, ANGPTL4, aPL) depending on eGFR in groups of RA patients without signs of metabolic syndrome and RA patients with MetS. Significant differences in the level of ANGPTL3 (F = 8.86, p = 0.0034) and ANGPTL4 (F = 29.6, p < 0.001), but not aPL (p > 0,05) were found between RA patients with varying degrees of severity of metabolic disorders.Multivariable analysis of variance showed a significant increase in ANGPTL4 in the blood serum of RA patients with reduced eGFR (< 89 ml/min) (F = 18.5, p < 0.001) and pronounced metabolic changes (F = 24.2, p < 0.001). Thus, only two factors (renal dysfunction and the presence of MetS) had a direct effect on the ANGPTL4 content in RA patients, which could describe the variability of this sign in more than 30% of cases. The squared multiple correlation coefficient (R2 ) in this model was 0.33. ANGPTL type 4 should be considered as a key factor linking the development of renal dysfunction and metabolic changes caused by rheumatoid inflammation.